Management of zygomatic-maxillary fracture (The principles of diagnosis and surgical treatment with a case illustration) - David B. Kamadjaja; Coen Pramono D (Dental Journal (Majalah Kedokteran Gigi), 2008)
Mechanical trauma to the face may cause complex fracture of the zygoma and the maxilla. The characteristic clinical signs of zygomatic bone fracture include flattening of the cheek, infraorbital nerve paraesthesia, diplopia, and trismus, whereas maxillary fracture may typically cause flattening of the midface and malocclusion. The diagnosis of zygomatic and maxillary fracture should be established with thorough clinical examination and careful radiologic evaluation so that a three-dimensional view of the fractured bones can be obtained. This is essential in order to plan a proper surgical treatment to reconstruct the face in terms of functions and aesthetic. A standard surgical protocol should also be followed in performing the surgical reconstruction of the zygoma and the maxilla. A case of delayed bilateral fracture of zygoma and maxilla is presented here to give illustration on how the principle of diagnosis and surgical treatment of complex zygomatico-maxillary fracture are applied.